Implementasi Program Wajib Belajar PLS di Desa Tertinggal - Zainun Zainun (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
This study is an effort to understand the implementation of the PLS program and factors influencing the advantages and disadvantages in applying the program. The sample consisted of officials of the Department of Education and formal and informal leaders in South Kalimantan related to the compulsory education. Data were gathered by using questionnaire and interview, and documentary analysis. The results revealed that the implementation the out-of-school program faced some problems concerning with social and cultural background. The learners joined the program to get knowledge and expand their skills, while others were not interested in it and assumed that the program was non relevant to their daily needs.